1991
DOI: 10.1007/bf02470968
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the acute phase protein levels in patients with esophageal cancer

Abstract: Based on the findings that the enhancement of serum alpha 2-macroglobulin (A2M) is associated with the occurrence of infectious complications following surgery in patients with esophageal cancer, we examined possible factors which could contribute to the alterations of serum acute phase protein levels in patients with this disease. A multiple linear regression analysis was made for 71 patients with esophageal cancer and 58 with gastric cancer. In patients with esophageal cancer, protein calorie malnutrition (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…29 In humans, data in cervical, esophageal, and colorectal cancer suggest that AGP concentration does correlate with clinical stage of disease. 5,15,16 Stage of disease was not assessed in the present study. Although differences among carcinomas, sarcomas, and discrete cell tumors were not significant in the present study, tumor type may have an influence on AGP concentration.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…29 In humans, data in cervical, esophageal, and colorectal cancer suggest that AGP concentration does correlate with clinical stage of disease. 5,15,16 Stage of disease was not assessed in the present study. Although differences among carcinomas, sarcomas, and discrete cell tumors were not significant in the present study, tumor type may have an influence on AGP concentration.…”
Section: Discussionmentioning
confidence: 95%
“…AGP concentrations have been found to be increased in both dogs and humans in a variety of illnesses, including acute and chronic inflammation, pregnancy, and cancer. [1][2][3][4][5]9,[11][12][13][14][15][16][17][18][19][20][21][25][26][27][28] Although its role in such processes remains unclear, AGP has been shown to be an important marker in monitoring therapy of human cancer patients. 1,4,16,20 A similar pattern may occur in dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some of neighboring DEGs were also reported aberrant expression in ESCC. The upregulated DEG of A2M, the downregulated DEGs of DCN and TGFB1 are found enhanced in ESCC252627. Our previous study showed found SDC2 mRNA down-regulation in ESCC is related to a poor prognosis28.…”
Section: Disscussionmentioning
confidence: 79%
“…Synthesis of acute phase reactive proteins like that of albumin, is also impeded by protein malnutrition [59,60] even following an appropriate inflammatory stimulus ( fig. 1).…”
Section: Role Of Cytokines On Appetite and Body Compositionmentioning
confidence: 99%